Recreational activities as a mediator in learning english language vocabulary - Campoverde Paladines, Kevin Ariel; Celi Fajardo, Brenda Scarlett (Machala : Universidad Técnica de Machala, 2021)
The present research analyzes the relationship between the implementation of recreational activities and the learning of vocabulary in the English language through the use of virtual educational games for the improvement of learning by second-semester students of the Pedagogy of National and Foreign Languages career of the Universidad Técnica de Machala (UTMACH), through quantitative methods such as semi-structured interview, participant observation, and a pedagogical test. The investigation follows a non-experimental, qualitative design with an action- research approach with a biased selection that consisted of three university students between 19 and 20 years old from the second semester. The research development indicates significant improvements between the implementation of the ludic and the teaching of a new language. Therefore, it is possible to acquire a vast vocabulary that will generate bases for their future career's performance. In addition, a checklist was applied to corroborate our intervention approach, and as a result, there are very noticeable differences between the teaching previously given and that implemented with new methodological strategies based on recreation and virtual games implementation.
El presente trabajo se analiza la relación que existe entre la implementación de actividades lúdicas y el aprendizaje de vocabulario del idioma inglés, en la utilización de juegos virtuales educativos para la mejora del aprendizaje en estudiantes de segundo semestre de la carrera de Pedagogía de los Idiomas Nacionales y Extranjeros de la Universidad Técnica de Machala (UTMACH), a través de métodos empíricos tales como: entrevista semiestructurada, observación participante y una prueba pedagógica. La investigación sigue un diseño no experimental, cualitativa con un enfoque de investigación-acción con una muestra opinática de estudiantes universitarios de edades entre 19 a 20 años de edad, en un grupo selecto de 3 estudiantes del segundo semestre. Mediante el desarrollo en la investigación se indica que, existe mejoras significativas entre la implementación de la lúdica y la enseñanza de un nuevo idioma, es así que se podrá lograr la adquisición de un amplio vocabulario que generará bases para su futuro en el desempeño de la carrera. Además, se aplicó un checklist para corroborar nuestra propuesta de intervención y como resultado se señala diferencias bien notables entre la enseñanza antes dada y la implementada con nuevas estrategias metodológicas, por medio de la recreación y en la implementación de juegos virtuales.
Keywords: RECREATION; IMPLEMENTATION; TEACHING